The Effect of Processing on Bioactive Compounds and Nutritional Qualities of Pulses in Meeting the Sustainable Development Goal 2 - Acquah, Caleb; Ohemeng-Boahen, Godfred; Power, Krista A.; Tosh, Susan M. (Frontiers in Sustainable Food Systems, 2021)
Diversification of plant-based food sources is necessary to improve global food and nutritional security. Pulses have enormous nutritional and health benefits in preventing malnutrition and chronic diseases while contributing positively to reducing environmental footprint. Pulses are rich in diverse nutritional and non-nutritional constituents which can be classified as bioactive compounds due to their biological effect. These bioactive compounds include but are not limited to proteins, dietary fibres, resistant starch, polyphenols, saponins, lectins, phytic acids, and enzyme inhibitors. While these compounds are of importance in ensuring food and nutritional security, some of the bioactive constituents have ambivalent properties. These properties include having antioxidant, anti-hypertensive and prebiotic effects. Others have a deleterious effect of decreasing the digestibility and/or bioavailability of essential nutrients and are therefore termed antinutritional factors/compounds. Various processing techniques exist to reduce the content of antinutritional factors found in pulses. Traditional processing of pulses comprises soaking, dehulling, milling, germination, fermentation, and boiling, while examples of emerging processing techniques include microwaving, extrusion, and micronization. These processing techniques can be tailored to purpose and pulse type to achieve desired results. Herein, the nutritional qualities and properties of bioactive compounds found in pulses in meeting the sustainable development goals are presented. It also discusses the effect of processing techniques on the nutritional and non-nutritional constituents in pulses as well as the health and environmental benefits of pulse-diet consumption. Major challenges linked to pulses that could limit their potential of being ideal crops in meeting the sustainable development goal 2 agenda are highlighted.